Moving forward with treatment options for HIV-infected children. (2nd January 2018) - Beghin, Jean-Christophe; Yombi, Jean Cyr; Ruelle, Jean; Van der Linden, Dimitri
ABSTRACT: Introduction : Current international guidelines recommend to treat all HIV-1 infected patients regardless of CD4 cell count. Despite the remarkable worldwide progress for universal access to antiretroviral during the last decade, the pediatric population remains fragile due to lack of randomized studies, inappropriate antiretroviral formulations, adherence difficulties, drug toxicity and development of resistance. Areas covered : This review summarizes the latest recommendations and advances for the treatment of HIV-infected children and highlights the potential complications of a lifelong antiretroviral treatment initiated early in life. Expert opinion : International guidelines recommend to start combination antiretroviral therapy (cART) as fast as possible in all children diagnosed with HIV-1. The principal goal is to improve survival and reduce mortality as well as rapidly decrease HIV reservoirs. This remains a challenge in resource-limited settings were diagnostic tools and treatment access may be limited. Different new strategies are in the pipeline such as immunotherapy in combination with very early cART initiation to seek remission or functional cure. For the time being and awaiting for long term remission or cure, there is a need for further pharmacokinetics studies, more pediatric formulations with improved palatability and implementation of randomized trials for the newer antiretroviral drugs.